2021
DOI: 10.3389/fonc.2021.678896
|View full text |Cite
|
Sign up to set email alerts
|

Curative Effect and Survival Assessment Comparing Gemcitabine and Cisplatin Versus Methotrexate, Vinblastine, Doxorubicin and Cisplatin as Neoadjuvant Therapy for Bladder Cancer: A Systematic Review and Meta-Analysis

Abstract: BackgroundNeoadjuvant chemotherapy has been accepted as an effective curative treatment for muscle-invasive bladder cancer patients and has resulted in better survival outcomes than radical cystectomy or a cisplatin-based regimen. In the present study, we aimed to compare the two most commonly used cisplatin-based neoadjuvant chemotherapies, gemcitabine plus cisplatin and methotrexate plus vinblastine plus doxorubicin plus cisplatin, by summarizing and analyzing clinical data and outcomes of published research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The role of NAC in the treatment of bladder cancer should be further investigated. Recent reports described the efficacy of NAC in bladder cancer [38,39], with the number of cases strongly increasing. However, whether all patients with MIBC should receive NAC is controversial [40].…”
Section: Discussionmentioning
confidence: 99%
“…The role of NAC in the treatment of bladder cancer should be further investigated. Recent reports described the efficacy of NAC in bladder cancer [38,39], with the number of cases strongly increasing. However, whether all patients with MIBC should receive NAC is controversial [40].…”
Section: Discussionmentioning
confidence: 99%
“…Another phase III randomized controlled trial (RCT) concluded that MVAC and GC had comparable clinical effects, with the GC protocol having better tolerance and safety ( 15 ). Similarly, a meta-analysis of 3,116 patients from 18 studies found no statistical difference between GC regimen and MVAC regimen in terms of pCR and OS (P=0.69, P=0.87) ( 16 ). In general, the GC regimen has fewer side effects and better tolerance than the dd-MVAC regimen, but the latter has a higher rate of local control and clear advantages in pathological reaction.…”
Section: Neoadjuvant Chemotherapy (Nac)mentioning
confidence: 99%
“…Doxorubicin can treat various types of cancer, including leukemia, lymphoma, soft tissue sarcomas, and solid tumors. Its cytotoxic effect is desirable on malignant cells; on the contrary, there is the potential for undesirable cardiotoxic effects [ 7 , 8 , 9 , 10 , 11 ], so cardiac protection is needed, which can contribute to heart preservation by reducing or even preventing heart damage [ 12 , 13 , 14 ]. The cardioprotective effects of several plants have recently been widely studied, one of which is to minimize the cardiotoxic potential of doxorubicin.…”
Section: Introductionmentioning
confidence: 99%